THE INFLUENCE OF LIFESTYLE AND FAMILY ATTITUDES REGARDING LATRINES IN PAYA SEUMANTOK VILLAGE, KRUENG SABEE DISTRICT, ACEH JAYA REGENCY 2023 - Kala, Pasyamei Rembune; Wahyu, Reski; Mustafa, Diana (Transpublika Publisher, 2023)
Nationally, only 39% of households use healthy habits, in urban areas (60%) it is higher than in rural areas (23%). The use of latrines is an important health problem in rural areas such as Paya Seumantok Village in Aceh Jaya Regency. Only 19.8% of households have their own toilet in Sukadunia Village. The sample was 196 housewives with children under five, which was carried out in November-December 2023. Data collection was carried out by direct interviews using a questionnaire. The research results showed that only 46.4% of families used latrines, while those who did not use latrines (53.6%) generally used rivers (55.2%) and ponds (38.1%) as a means of defecating. All the variables studied were significantly related, including education, knowledge, attitudes, latrine ownership, clean water facilities, development of community health center officers and support from village officials, Posyandu cadres & NGOs for latrine use. latrine with OR = 27.03 (5.224 – 139.912).